2016
DOI: 10.1007/s11126-016-9429-z
|View full text |Cite
|
Sign up to set email alerts
|

PTSD’s Underlying Dimensions in Typhoon Haiyan Survivors: Assessing DSM-5 Symptomatology-Based PTSD Models and Their Relation to Posttraumatic Cognition

Abstract: The recent changes in posttraumatic stress disorder (PTSD) symptomatology in the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) call for a re-examination of PTSD's latent factor structure. The present study assessed six competing models of PTSD based on DSM-5 symptomatology using confirmatory factor analysis in a sample of young adult Filipino survivors of typhoon Haiyan, one of the strongest typhoons in the world ever recorded at the time of its landfall (N = 632). Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 56 publications
2
18
2
Order By: Relevance
“…However, the statistical comparisons of nested models revealed that the 7-factor Hybrid model did not fit significantly better than the 6-factor Anhedonia model. This result diverges from most of the extant literature assessing the fit of the Hybrid model (Armour, Contractor et al, 2016; Armour et al, 2015; Bovin et al, 2015; Mordeno et al, 2016; Seligowski & Orcutt, 2015; Zelazny & Simms, 2015), but it is consistent with Carragher et al's (2016) and Wang et al's (2015) studies, which also reported similar values of fit indices across the models and found no significant differences in model comparisons between the Anhedonia and Hybrid models. As Carragher et al (2016) suggested, this divergence with previous studies may be related to sample characteristics.…”
Section: Discussioncontrasting
confidence: 75%
See 4 more Smart Citations
“…However, the statistical comparisons of nested models revealed that the 7-factor Hybrid model did not fit significantly better than the 6-factor Anhedonia model. This result diverges from most of the extant literature assessing the fit of the Hybrid model (Armour, Contractor et al, 2016; Armour et al, 2015; Bovin et al, 2015; Mordeno et al, 2016; Seligowski & Orcutt, 2015; Zelazny & Simms, 2015), but it is consistent with Carragher et al's (2016) and Wang et al's (2015) studies, which also reported similar values of fit indices across the models and found no significant differences in model comparisons between the Anhedonia and Hybrid models. As Carragher et al (2016) suggested, this divergence with previous studies may be related to sample characteristics.…”
Section: Discussioncontrasting
confidence: 75%
“…In this regard, in addition to the aforementioned considerations, the fact that some researchers suggest a possible effect of population type, trauma type, and PTSD measures on the model fit must be highlighted (Elhai & Palmieri, 2011). Furthermore, the high rate of probable PTSD diagnosis in our sample (67.3%) when compared to the rates in previous studies that assessed this model (ranging from 4.02 to 45.9%; Armour, Contractor et al, 2016; Armour et al, 2015; Carragher et al, 2016; Mordeno et al, 2016; Seligowski & Orcutt, 2015; Wang et al, 2015; Zelazny & Simms, 2015) might have contributed, to some extent, to the contradiction of our hypothesis. In fact, Biehn, Elhai, Fine, Seligman, and Richardson (2012) examined differences in PTSD's dimensional structure between Canadian veterans with and without a PTSD diagnosis and found that the models demonstrated a better fit in the sample who did not have a PTSD diagnosis.…”
Section: Discussioncontrasting
confidence: 43%
See 3 more Smart Citations